Expression 7: "y" equals StartFraction, left parenthesis, "c" plus "a" , right parenthesis Over "b" plus "d" , EndFraction "x"y=c+ab+dx
7
Label: left parenthesis, "b" , "a" , right parenthesisb,a
Label:
equals=
left parenthesis, 3 , 4 , right parenthesis3,4
8
Label: left parenthesis, "d" , "c" , right parenthesisd,c
Label:
equals=
left parenthesis, 5 , 2 , right parenthesis5,2
9
Label: left parenthesis, "b" plus "d" , "a" plus "c" , right parenthesisb+d,a+c
Label:
equals=
left parenthesis, 8 , 6 , right parenthesis8,6
10
Expression 11: left parenthesis, "y" minus "c" , right parenthesis equals left parenthesis, StartFraction, "a" Over "b" , EndFraction , right parenthesis left parenthesis, "x" minus "d" , right parenthesis left brace, "d" less than or equal to "x" less than or equal to "b" plus "d" , right bracey−c=abx−dd≤x≤b+d
11
Expression 12: left parenthesis, "y" minus "a" , right parenthesis equals left parenthesis, StartFraction, "c" Over "d" , EndFraction , right parenthesis left parenthesis, "x" minus "b" , right parenthesis left brace, "b" less than or equal to "x" less than or equal to "b" plus "d" , right bracey−a=cdx−bb≤x≤b+d